Validation of Palaemon audouini Heller, 1861 (Crustacea: Decapoda: Palaemonidae), an overlooked species from the Red Sea. Issue 4 (1st October 2020) - De Grave, Sammy; Ashelby, Christopher W.
Abstract : The shrimp species Palaemon audouini Heller, 1861, described from the Red Sea, has long been considered a nomen dubium but examination of the type material in the zoological collections of the Naturhistorisches Museum in Wien, Austria determined that it represents a valid species. It is morphologically close to the widespread P. pacificus, but can be distinguished by the length of the chela of the second pereiopod in relation to the carpus, and details of the scaphocerite and rostrum. The known Palaemon fauna of the Red Sea is briefly reviewed and reasons why the species could have been overlooked for so long are discussed.